2017
DOI: 10.1136/archdischild-2016-311530
|View full text |Cite
|
Sign up to set email alerts
|

An alternative sensor-based method for glucose monitoring in children and young people with diabetes

Abstract: ObjectiveTo determine accuracy, safety and acceptability of the FreeStyle Libre Flash Glucose Monitoring System in the paediatric population.Design, setting and patientsEighty-nine study participants, aged 4–17 years, with type 1 diabetes were enrolled across 9 diabetes centres in the UK. A factory calibrated sensor was inserted on the back of the upper arm and used for up to 14 days. Sensor glucose measurements were compared with capillary blood glucose (BG) measurements. Sensor results were masked to partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
136
5
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(168 citation statements)
references
References 34 publications
19
136
5
8
Order By: Relevance
“…In our study 76.2% of the hypoglycaemias and 93.8% of the hyperglycaemias were detected by the FGM. This is better than in the study of Edge et al [25] were 70% of the hypoglycaemias were detected and 85% of the hyperglycaemias.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…In our study 76.2% of the hypoglycaemias and 93.8% of the hyperglycaemias were detected by the FGM. This is better than in the study of Edge et al [25] were 70% of the hypoglycaemias were detected and 85% of the hyperglycaemias.…”
Section: Discussioncontrasting
confidence: 51%
“…In adults, Baily et al [20], found 99.7% and Fokkert et al [35] found 99.8% of the results in zone A and B. It is noteworthy to mention that Edge et al [25] and Baily et al [20] compared the scanned SG values with the capillary BG levels determined by the build-in meter using FreeStyle Optium test strips. Szadkowska et al [27] used the Contour Plus One glucometer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed clinical benefits of flash glucose monitoring use in pediatric patients with T1D. [22][23][24] The clinical implications of CGM use to prevent hypoglycemia in children with T1D and other metabolic disorders were highlighted in this supplement by Lal et al 25 We hope that flash glucose monitoring (FreeStyle Libre personal) will be made available soon in the United States after approval by the FDA. We also hope that it is approved as ''nonadjunctive,'' since most providers and patients do not use current CGMs as adjunctive.…”
mentioning
confidence: 99%
“…Indeed, several studies have confirmed high levels of patient satisfaction with the FSL in adult and paediatric populations. [2][3][4] The IMPACT study, the major randomised controlled trial assessing the FSL, also described higher rates of treatment satisfaction. 5 …”
Section: User Satisfactionmentioning
confidence: 99%